A Novel Dual Magnetodiode for Wireless Sensor Networks - Chalin Sutthinet; Amporn Poyai; Toempong Phetchakul (My University, 2020)
This paper presents a new magnetodiode, the so-called dual magnetodiode, for wireless sensor application. The device is a current mode which can be integrated with a chip compatible with modern low power, low voltage integrated circuit (IC). The structure and operation are completely different from a conventional magnetodiode. The structure is composed of two p–n junctions in that one region is common and the others are split terminals for output of differential current. The underlying mechanism is carrier deflection by induced force from a magnetic field. The carriers are injected from the common region by forward bias. The defection carriers diffuse, deflect, and recombine along substrate through split terminals according to direction and density of the magnetic field linearly and symmetrically. From the comparison of complementary structure of the split cathode and the split anode structure of LD = 50 μm, the bias current 1 mA and magnetic field 0.5 T, the relative sensitivities (SR) are 11.01 and 11.19 T−1, respectively. This device is a simple p–n junction structure which is compatible with all micro/nanotechnology.
Keywords: Biasing; Magnetic Field Sensors Techniques